Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning Terintegrasi Kearifan Lokal Bali pada Materi Tumbuhan di Kelas IV SD Negeri 1 Pengotan - Widiani, Ni Wayan (Universitas Muhammadiyah Mataram, 2025)
This study aims to identify (1) the needs of teachers regarding student worksheets (LKPD), (2) the prototype of student worksheets (LKPD), (3) the feasibility of student worksheets (LKPD) based on Problem Based Learning integrated with the local wisdom of Bali. This research is a type of R&D (Research and Development) involving potential and problem analysis, data collection, product design, validation, and revision. The subject of the research is fourth-grade teachers, and the object of this research is the problem-based learning (PBL) student worksheets integrated with local wisdom. The data collection techniques in this study are interviews and questionnaires, with instruments in the form of interview sheets and questionnaires. The data analysis of the research uses descriptive statistics. Based on the interview results, it can be concluded that teachers need student worksheets to support the learning process in schools to encourage student participation in class and motivate students to learn. The design of the student worksheets developed consists of a title, introduction, materials and sources, stages of activities, questions, and evaluation. The validation results show an average score of 89, categorized as valid, thus the student worksheets based on Problem-Based Learning integrated with local Balinese wisdom are deemed suitable for use.